Forgiveness and politics : a critical appraisal - Kevichusa, Kethoser Aniu (Regnum Books International, 2021)
It is often assumed that forgiveness and politics are unrelated and unrelatable. This work, however, explores and argues for the deep and intrinsic relation between forgiveness and politics. It does so by exploring biblical foundations of forgiveness, and the concepts and practices of politics, justice, and reconciliation, arguing that these concepts and practices are themselves undergirded and sustained by forgiveness. Studies of the conflicts in Northern Ireland and Nagaland also illuminate and illustrate the discussion.